Perceptions of Principals towards the Professional Development of Primary Mainstream School Teachers of the Netherlands - Gopalakrishnan, Lakshmi (International Journal of Scientific Research and Management (IJSRM), 2016)
Professional development is crucial for teachers in improving the education of children with special educational needs in themainstream schools. This study took a qualitative approach to examine the perceptions of the principals who are also responsible for theprofessional development of teachers in the mainstream primary schools of the Netherlands. The data was collected through semi-structuredinterviews and a questionnaire from four principals selected by convenience sampling. The questionnaire was used for data triangulation.The findings indicate that the principals perceived that most of the teachers have adequate professional development in educating childrenwith mild to moderate difficulties. However, the principals expressed that the teachers have difficulty in establishing parent-teachercollaboration as well as managing children with emotional and behavioral problems and severe disabilities. The principals in this studyopined that collaborative learning was an effective professional development activity followed by reflective practice, action research andshort-term training courses. Further analysis of data showed qualities related to educational, transactional and transformational leadershipstyles in the approaches followed by the principals to stimulate the professional development of teachers.